A systematic review of progress in food security research and implications for achievement of the UN’s zero-hunger goal in Bangladesh - Abdul Mohammed Mokter Hossain; Md Sarwar Hossain; Cecilia Tortajada (Environmental Research: Food Systems)
Despite numerous policy initiatives to achieve food security, more than 2 billion people are food insecure across the world. Food security research can help addressing food insecurity effectively by summarizing the state of knowledge and providing future research direction to make sure no one is left behind. Yet, there are no comprehensive studies of food security research in Global South countries such as in Bangladesh, where nearly one-third of the population is food insecure. Here, this systematic review aims to identify the progress, gaps, and future research directions for food security in Bangladesh by investigating current research trends and the influence of socioeconomic and environmental drivers on food security and recommend policy interventions for achieving the zero-hunger goal of the Sustainable Development Goals (SDGs). We systematically reviewed articles both quantitatively and qualitatively and summarized the trends, methods, challenges, and opportunities of food security research in Bangladesh. Our findings reveal that longitudinal trends and inequality in food security across administrative and agroecological zones are underexplored. Moreover, most studies focused on the influence of socioeconomic drivers, with insufficient attention to environmental drivers, and none examined the causal relationships among them. The access and availability dimensions of food security are the most studied, while stability and utilization are the least addressed in food security research. Addressing these gaps is essential for establishing a sustainable food system that may help Bangladesh achieving the SDG target of ending hunger (SDG 2) and ensuring no one is left behind.